Polska perspektywa Koncepcji – Praca 4.0 - Błażewski, Maciej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The Concept - Work 4.0 was adopted in Germany. It is a set of priorities related to protection of employee, which are relating to technological and economic changes. In Poland, the Concept - Work 4.0 is limited to ensuring effective implementation of the employer’s goals.
Keywords: Work 4.0; Employer; Employee; Technological development